A silent scream: trauma and madness in the early works of António Lobo Antunes - Rato Rodrigues, Ricardo (2016)
Intersection between Literature and Health Sciences, the current thesis is dedicated to the analysis of the early work of influential Portuguese novelist António Lobo Antunes. His multifaceted roles - as psychiatrist, soldier and writer - inform his literary production, in particular the semi-autobiographical novels Memória de Elefante (Elephantine Memory), Os Cus de Judas (Land at the End of Nowhere) and Conhecimento do Inferno (Knowledge of Hell), as well as his letters and chronicles. The thesis looks at the different ways in which Lobo Antunes' oeuvre articulates the different perspectives within the contexts of mental institutions and war. Issues such as trauma (individual and collective), PTSD (post-traumatic stress disorder) and the cathartic role of writing are analysed in detail. The brutal and traumatic realities of war and post-colonial trauma are intertwined in the novels in the intricate and complex writing that is characteristic of Lobo Antunes. His writing ethos elicits an active participation from the reader - an act of participatory reading which aims for the broadening and better understanding of human experiences via empathy. The writer's importance is not only relevant for the Portuguese context. Despite his close attention to the troublesome tradition of Portuguese psychiatry (i.e. the invention of lobotomy by Dr. Egas Moniz, who was awarded the Nobel prize in Medicine for such discovery) and the country's recent belligerent and oppressive history (the dictatorial regime and the Colonial War), Lobo Antunes' novels have universal qualities, in the Joycean tradition of the 'universality of the local', which gives his work validity and urgency.